Taking on the Taliban: Ethical issues at the frontline of academia - Ahmad, Ayesha (Bioethics, 2019)
This article reflects on the challenges of developing academic research that is undertaken to create social change. I describe the ways that my research has been generated and guided by activism. Even though the descriptor of my research interests is generally gender-based violence and mental health, my research is situated within an ongoing political discourse that fundamentally opposes and normatively challenges ideologies such as those implemented at a governmental level during the Taliban regime in Afghanistan that continue to have power over Afghan women’s lives. I critique the emergence of two research projects that work with women survivors of violence and develop trauma therapeutic interventions using traditional storytelling. My positionality as a woman of Muslim origin and an academic in the U.K. resulted in inescapable juxtapositions and the necessary blurring of the boundaries between personal and professional viewpoints as well as highlighting the potency of traumatic stories in contexts of conflict, oppression, silencing and marginalization. I go on to explain why I have a moral obligation as an ethicist working in global health, with resources and expertise, to systematically develop my research questions and objectives in accordance with the end-goal of tackling and deconstructing harmful ideologies and practices towards women and girls in societies marred by the violent complexities of national and international conflicts.